CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon
MyQuestionIcon
Question

If 1/a + 1/b + 1/c = 1/(a+b+c), where a+b+c and a*b*c is not equal to zero then what's the value of

(a+b)(b+c)(c+a)

Open in App
Solution

1/a + 1/b + 1/c =1/ (a+b+c)
=> 1/a + 1/b =1/ (a+b+c) - 1/c
=> (b+a)/ab = (c - (a+b+c)) / c(a+b+c)

Cross multiplying (Since, a,b,c !=0 and a+b+c != 0)

=> c(a+b+c)(b+a) = -ab(a+b)
=>
(a+b)( ca +cb +cc + ab ) = 0
=> (a+b)( ca + cc + cb + ab) = 0
=> (a+b)(b+c)(c+a)=0

flag
Suggest Corrections
thumbs-up
17
Join BYJU'S Learning Program
similar_icon
Related Videos
thumbnail
lock
Evaluation of Determinants
MATHEMATICS
Watch in App
Join BYJU'S Learning Program
CrossIcon